Secure Cloud Data Sharing Using Key-Aggregate Cryptosystem - Mathew, Ms.Minimol; Sumathi, Mrs. D; Ranjima, Ms. P; Sivaprakash, Mr. P (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is used to store and share data by anyone from anywhere in the world. It provides scalable and on demand self services. The cloud data expect maximum security at rest state as well as at transit state. Service providers provide security to the data in the cloud and the data owner also uses some cryptographic techniques for data security. They may use symmetric cryptography or asymmetric cryptography. If the data owner use same cryptographic key for all data files, they cannot share the partial amount of data files. Because of that the owner using the separate encryption/ decryption keys for each file in the cloud. Here to provide security and avoid network burden, the data owner can aggregate all decryption keys into a single key. This aggregate key can decrypt any subset of delegated cipher text blocks.